Hubungan antara Kelekatan dengan Interaksi Sosial pada Siswa - Puteri, Maharani; Wangid, Muhammad Nur (Universitas Ahmad Dahlan, 2017)
This study aimed to find the correlation between proximity and social interaction. This was a correlational study. The population of this study was 173 eight grade students. The data were collected by using proximity scale and social interaction scale. To analyze the data, this study used product moment correlation. The result of this study showed that there was a positive and significant correlation between proximity and social interaction by the coefficient of correlation (r) 0.365 and p = 0.000 (p < 0.05). In other words, higher proximity leads to higher social interaction and vice versa. The results of this study can provide information to educators, especially guidance and counseling teachers (BK) as predictions and preliminary data before providing guidance and counseling services to develop students proximity Â and social interaction.